New Traits of Agriculture/Food Quality Interface - Durazzo, Alessandra (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
There is a close link between food and territory. The current challenges are located in precision agriculture and food metrology from the perspective of monitoring and improving food quality, and addressing the promotion of diversity of agroecosystems and diets. Research studies describing factors affecting food quality-such as agronomic conditions, post-harvest elicitors, cultivar selection, harvest date, or environmental influences-are welcome. Sustainable environmental and innovative practices should be promoted. Advanced techniques, such as mass spectrometry, infrared, and Raman spectroscopy in the monitoring and control of foodstuffs to model the agrofood system should be considered. Innovative green technologies should be taken into account. Targeting food approaches should be promoted. Chemometrics applications are welcome. This issue promotes highly interdisciplinary studies, including disciplines from agriculture and biology, chemistry, and nutrition. All types of articles, such as original research, opinions, and reviews, are welcome.